2023
DOI: 10.1002/smll.202303693
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Production of Glycolate Fuelled By Polyethylene Terephthalate Plastics with Improved Techno‐Economics

Abstract: Electrochemical valorization of polyethylene terephthalate (PET) waste streams into commodity chemicals offers a potentially sustainable route for creating a circular plastic economy. However, PET wastes upcycling into valuable C2 product remains a huge challenge by the lack of an electrocatalyst that can steer the oxidation economically and selectively. Here, it is reported a catalyst comprising Pt nanoparticles hybridized with γ‐NiOOH nanosheets supported on Ni foam (Pt/γ‐NiOOH/NF) that favors electrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…Therefore, commercial PET granules were first depolymerized into a PET hydrolysate via alkaline hydrolysis (1.5 M KOH), which was subsequently utilized as a feedstock for the photocatalytic reaction. 48 As illustrated in Fig. 4a, the average H 2 evolution rate over O-CuIn 5 S 8 is 2.57 ± 0.02 mmol g −1 h −1 , which is about 7 times higher than that of pristine CuIn 5 S 8 (0.36 ± 0.02 mmol g −1 h −1 ), indicating the enhanced photocatalytic activity after oxygen incorporation into the photocatalyst.…”
Section: Resultsmentioning
confidence: 85%
“…Therefore, commercial PET granules were first depolymerized into a PET hydrolysate via alkaline hydrolysis (1.5 M KOH), which was subsequently utilized as a feedstock for the photocatalytic reaction. 48 As illustrated in Fig. 4a, the average H 2 evolution rate over O-CuIn 5 S 8 is 2.57 ± 0.02 mmol g −1 h −1 , which is about 7 times higher than that of pristine CuIn 5 S 8 (0.36 ± 0.02 mmol g −1 h −1 ), indicating the enhanced photocatalytic activity after oxygen incorporation into the photocatalyst.…”
Section: Resultsmentioning
confidence: 85%
“…In our recent work, to highlight the advantages of a Pt/NiOOH heterostructure for the selective transformation of ethylene glycol to glycolic acid with respect to bare Pt and NiOOH, the adsorption ability and the reaction pathway are calculated. 211 As shown in Fig. 11a, the Pt/NiOOH interface enabled the lowest adsorption energy for ethylene glycol among all the models, indicating the favorable reactant adsorption process over Pt/NiOOH.…”
Section: Mechanism Investigationmentioning
confidence: 85%
“…210 However, glycolic acid generation with high selectivity remains challenging due to the uncontrollable and severe C-C bond cleavage followed by the formation of formic acid during ethylene glycol oxidation. Currently, the selective conversion of ethylene glycol to glycolic acid is only enabled by noble metals, such as Pt, 211 Pd, 212 and Au. 213 A recent work from Shi et al 206 reported PdAg/NF electrocatalysts to evoke the transformation from ethylene glycol to glycolic acid with high selectivity and faradaic efficiency (Fig.…”
Section: Ethylene Glycolmentioning
confidence: 99%
“…[10][11][12][13] To date, Pt-based materials are still recognized as benchmark catalysts for the alkaline HER owing to the favorable kinetics for water dissociation over Pt sites. However, their large-scale deployment is significantly obstructed by the low earth abundance and high cost, [14][15][16][17] necessitating the exploration of alkaline HER catalysts with enhanced activity and economic applicability.…”
Section: Introductionmentioning
confidence: 99%